Analysis of the world experience of forming agricultural territories within spatial planning - Butenko, E.; Loshakova, Y. (Land Management, Cadastre and Land Monitoring, 2019)
Abstract. The land management method is the main instrument for the organization of sustainable use and protection of land in the process of agricultural land use formation in spatial planning of territories. It is important to consider the effectiveness of the existing land management system as an ecological and economical tool for sustainable development of the agrarian sector. The discussion of the formation of highly efficient agricultural land use in Ukraine is conducted while reviewing the world positive experience regarding the realization of the main principles of the spatial planning of territories. In this study, the international experience of land-use planning is analyzed with sustainable use of agricultural lands taken into the account. A core of the main spheres of implementation of the world experience in spatial planning of the territories is reviled with consideration of ecological and economical mechanisms of sustainable use of lands in Ukraine . In this paper, I(we) will study the international experience of using land management mechanism for providing sustainable use of agricultural lands that are based on spatial planning of rural areas as independent objects of management. Keywords: sustainable development, spatial planning, decentralization, territorial community, region